Diagnostic value of lacrimal scintigraphy in the evaluation of lacrimal drainage system obstruction: a systematic review and meta-analysis. Issue 8 (4th May 2022) - Mirshahvalad, Seyed Ali; Chavoshi, Mohammadreza; Bahmani Kashkouli, Mohsen; Fallahi, Babak; Emami-Ardakani, Alireza; Manafi-Farid, Reyhaneh
Abstract : Purpose: A systematic review and meta-analysis to evaluate the diagnostic performance of lacrimal scintigraphy (LS) versus anatomical methods in the evaluation of the nasolacrimal duct obstruction (NLDO). Materials and methods: A systematic search was performed using electronic bibliographic databases until the end of May 2021. Inclusion criteria: (a) used LS as a diagnostic method to evaluate NLDO; (b) used anatomical studies [including syringing, irrigation, probing, and dacryocystography (DCG)] as reference tests; and (c) provided adequate crude data. A hierarchical method was used to pool the sensitivity and specificity. The hierarchical summary receiver-operating characteristic model was performed. Additionally, the studies' heterogeneity and publication bias were analyzed. All analyses were conducted by the 'Midas' module of STATA 16. Results: Twelve articles (with 14 separate populations) were considered eligible to enter the meta-analysis. They were divided into two groups based on the reference standard method, called irrigation and DCG groups. In the irrigation group, the pooled sensitivity and specificity were 89% [95% confidence interval (CI), 72–96%] and 25% (95% CI, 8–56%), respectively. In DCG group, the pooled sensitivity and specificity were 97% (95% CI, 85–100%) and 27% (95% CI, 0.12–0.49), in turn. Conclusion: LS is a sensitive modality to evaluate the anatomical obstruction of NLD. In contrast, it shows low pooled specificity compared with anatomical methods. Thus, LS can be used as the first noninvasive modality for the evaluation of epiphora. However, in case of any abnormality, confirmatory procedures are required.